Business model development for hospital pharmacy services case study: Edelweiss Hospital - Ahmad Meiyanto Wahyu Utomo; Astri Ghina (Goodwood Publishing, 2025)
Purpose: Innovation in healthcare is a key strategy for enhancing the competitiveness of Indonesian healthcare facilities. As one of the most complex and valuable hospital services, pharmacy services are the focus of this study, which aims to identify gaps between user profiles and provided services, determine value propositions, and develop a suitable business model Method: This study used a qualitative research methodology with a case study strategy and an abductive development approach. Data were collected through in-depth interviews with 6 (six) patients with outpatient insurance coverage and 6 (six) pharmacy staff members. Results: The study identified two main gaps in pharmacy services—long waits and lack of queue information—after testing the business model canvas with five patients and five pharmacists. Four value propositions emerged: faster service, transparent notifications, stock certainty, and improved patient experiences. Conclusion: The proposed business model canvas addresses the identified service gaps by offering targeted value propositions aimed at enhancing operational efficiency, improving service transparency, and elevating patient satisfaction with pharmacy services. Limitation: The study was limited to one healthcare facility with a small sample size, which may restrict the generalizability of the findings to other healthcare settings or regions. Contribution: This study contributes to healthcare service management by providing an empirically tested business model framework for pharmacy services that integrates patient and staff perspectives, offering actionable strategies to improve service delivery and competitiveness.